Presenting Windows Workflow Foundation : beta edition - Andrew, Paul; Conard, James M.; Woodgate, Scott; Flanders, Jon; Hatoun, George; Hilerio, Israel; Indurkar, Pravin; Pilarinos, Dennis; Willis, Jurgen (Sams Publishing, 2006)
Presenting Windows Workflow Foundation is a premium reference that provides information on a key part of WinFX, providing universally accessible and consistent workflow technology for the Windows platform. Windows Workflow Foundation delivers an API as part of WinFX and a workflow designer hosted in Visual Studio 2005. The Windows Workflow Foundation supports development of both sequential and state-based workflow involving both human and system interaction. Sequential workflow is a map of activities that may be in series or parallel. State-based workflow is a state machine where events cause transitions. Rules can be specified that drive decision making in a workflow and can be updated easily at runtime. Workflow can be created as a model and executed inside many host applications including Windows Forms, console applications, or Web applications.